Solid-state phase transformation kinetics in the near-equilibrium regime - Jiang, Yi-Hui; Liu, Feng; Wang, Jin-Cheng; Zhang, Zhong-Hua (Journal of materials science, 2015)
Solid-state phase transformation kinetics in the near-equilibrium regime behaves differently from that in extremely non-equilibrium regime since their thermodynamic states are different. Incorporating temperature- and transformed fraction-dependent thermodynamic terms, a thermo-kinetic model is derived to describe the transformation kinetics in the near-equilibrium regime. The model predicts a sluggish stage in isothermally conducted transformation and a temperature-dependent stage in non-isothermally conducted transformation. Then, the kinetics of γ / α transformations in two binary substitutional Fe-based alloys (i.e. Fe-3.28 at.% Mn and Fe-1.73 at.% Co), measured by isothermal and non-isothermal dilatometry, is investigated by the newly proposed model. The model quantitatively describes the retarded isothermal kinetics in Fe-3.28 at.% Mn alloy and the abnormal non-isothermal kinetics in Fe-1.73 at.% Co alloy.